The effect of gel formulated sildenafil on axially based rabbit skin flap survival - an experimental study - Luen, Koh Khai (2018)
Introduction Skin flap survival is one of the most important outcomes in reconstructive surgery. Various pharmacological agents have been studied previously with mixed results. Sildenafil has been shown to improved flap survival experimentally with variable dosing regimens and method of applications. The objective of this study is to determine the effect of our formulation of sildenafil gel that will be applied topically on the epidermal surface of rabbit skin flap to augment flap survival. Material and methods Six New Zealand rabbits (weight range 2.5-3.2kgs, 3 Female and 3 Male) were divided into 2 groups; control group (n=3) and treatment group (n=3). A standard protocol of perioperative care, anaesthesia, antibiotics, dressings and feeding regimen were followed. A standard oversized rabbit skin flap (14X5cm) based on superficial inferior epigastric vessels was designed and raised. Subsequently, the flaps were rendered to two hours of ischemic time with vascular clamp at the pedicle, released and flaps were sutured back. An aliquot of 1ml gel consisted of sildenafil (3mg) was applied immediately after surgery to the distal half of the flap in treatment group while on 1 mg gel without sildenafil was applied to control group. Measurements with Laser Doppler Flowmetry (LDF) at both distal and central flap were performed in all rabbit pre-surgery, post-operative day 1, 3, 5, 7 and 10. Area of necrosis of the skin flaps were measured using 2-plane planimetry and photographed. Mean flap survival in the treatment group was 99.59%, nearing total flap survival as compared to the control group of 85.96% with significant improvement in flap survival of 13.35% as compared to control group. Early and late blood flow improvements were observed at both central and distal part of flap with significant increased seen at distal flap on postoperative day 1 (133.50 PU treatment group versus 30.63 PU control group, p<0.05) and on central flap at postoperative day 10 (152.17 PU treatment group versus 84.93 PU control group, p<0.05). We postulated that sildenafil improved skin flap perfusion via early vasodilatory effects (within 72 hours) and late angiogenic effects (after 72 hours) of skin flap surgery. Conclusion The present study has demonstrated that with single application of gel formulated sildenafil (3mg), there was a significant improvement in rabbit’s skin flap survival via early and late increases of blood flow at the microcirculation.